Simulation of radionuclide diffusion in a dry storage of spent fuel under accident condition. (September 2018) - Chen, Liwei; Chen, Chunhua; Zheng, Xiaolei; Lin, Hanqing; Yin, Yuan; Long, Pengcheng
Abstract: The prediction of radionuclide diffusion is one of the indispensable factors for the nuclear emergency decision. So far, it is still short of an accurate simulation for the radionuclide diffusion in a spent nuclear fuel storage. Compared with the radionuclide diffusion in atmosphere, the airflow inside a dry-storage is always in turbulent state with a ventilation system, and diffusion process of radionuclide in the spent fuel dry storage is very complex. Therefore, a choice of an appropriate model is key point to estimate radionuclide dispersion in the dry storage. In this paper, the radionuclide concentration equation with the consideration of room wind field, wall condition and the features of radionuclide is updated to simulate the radionuclide dispersion in the spent fuel dry-storage with four vents. A three-dimensional model of radioactive concentration is obtained based on the standard k-ε turbulence model. The simulation results reveal that the standard k-ε turbulence model combined with updated radionuclide concentration equation gives a reasonable description for radionuclide diffusion under accident condition so as to provide more actual information for early emergency and consequence assessment. Highlights: The first signal at the vents can be predicted by the simulated trajectories. The temporal and spatial analysis of accidental radionuclide dispersion helps to reduce the leakage harm to the environment. The characteristics of the radionuclide dispersion at different leakage positions in a storage can be obtained by simulation. Emergency worker can predict the region of the radionuclide dispersion under the accident by numerical simulation.